Efeitos do isolamento social, estresse crônico imprevisível e do suporte social na acetilação e metilação de histonas em hipocampo de ratos de meia idade - Pires, Vivian Naziaseno (2022)
Studies suggest that social isolation is a potent stressor for social individuals, triggering physiological changes in the stress response, making the individual more vulnerable. Chronic Unpredictable Stress (CUS) is characterized by alternating different types of stressors at different times, causing behavioral, physiological and epigenetic changes. However, social support has been studied as a potential intervention to mitigate the negative effects of stressors. The alteration of histone acetylation and methylation patterns in middle-aged animals under adverse conditions shows consequences in the transcription of essential factors for the maintenance of the individuals homeostasis. The present study aimed to analyze the effects of social isolation, unpredictable chronic stress and social buffering on epigenetic mechanisms potentially involved in the modulation of neural plasticity in the hippocampus of middle-aged rats. Therefore, male Wistar rats (17 months of age, n=46) were divided into four experimental groups: Isolated (one animal per housing box), Stressed isolates (one animal per housing box subjected to daily stress), Accompanied (2 animals per housing crate) and Stressed Accompanied (two animals per housing crate, but only one of them was subjected to daily stress). Stressed animals were submitted to a CUS protocol for 30 days. The isolated and monitored animals without stress remained in their dwelling boxes for the same period. The hippocampus was collected and the acetylation and methylation of H3K9 and methylation of H3K27 were evaluated by Western Blotting and the corticosterone in the hair was analyzed by LC-MS/MS. Isolation decreased corticosterone levels and acetylation of H3K9, in addition to increasing its methylation levels. CUS also decreases H3K9 acetylation, in addition to increasing H3K27 methylation. There was also an interaction between the effects of housing type and treatment with the UHC protocol, so that the lowest levels of corticosterone were recorded for the animals isolated and submitted to UHC. Thus, it is concluded that social isolation in middle-aged animals is capable of inducing epigenetic changes potentially involved in the regulation of modulating factors, plasticity and neuronal survival. Additionally, this study also provides evidence that social support is able to buffer the negative effects of UHC on the HPA axis.